Down-regulation of MyoD gene expression in rat diaphragm muscle with heart failure - Lopes, Francis da Silva (Blackwell Publishing Ltd, 2008)
Diaphragm myopathy has been described in patients with heart failure (HF), with alterations in myosin heavy chains (MHC) expression. The pathways that regulate MHC expression during HF have not been described, and myogenic regulatory factors (MRFs) may be involved. The purpose of this investigation was to determine MRF mRNA expression levels in the diaphragm. Diaphragm muscle from both HF and control Wistar rats was studied when overt HF had developed, 22 days after monocrotaline administration. MyoD, myogenin and MRF4 gene expression were determined by RT-PCR and MHC isoforms by polyacrylamide gel electrophoresis. Heart failure animals presented decreased MHC IIa/IIx protein isoform and MyoD gene expression, without altering MHC I, IIb, myogenin and MRF4. Our results show that in HF, MyoD is selectively down-regulated, which might be associated with alterations in MHC IIa/IIx content. These changes are likely to contribute to the diaphragm myopathy caused by HF.